Ovine Hair Follicle Stem Cells Derived from Single Vibrissae Reconstitute Haired Skin - Zhang, Huishan (Int J Mol Sci, 2015)
Hair follicle stem cells (HFSCs) possess fascinating self-renewal capacity and multipotency, which play important roles in mammalian hair growth and skin wound repair. Although HFSCs from other mammalian species have been obtained, the characteristics of ovine HFSCs, as well as the methods to isolate them have not been well addressed. Here, we report an efficient strategy to obtain multipotent ovine HFSCs. Through microdissection and organ culture, we obtained keratinocytes that grew from the bulge area of vibrissa hair follicles, and even abundant keratinocytes were harvested from a single hair follicle. These bulge-derived keratinocytes are highly positive for Krt15, Krt14, Tp63, Krt19 and Itga6; in addition to their strong proliferation abilities in vitro, these keratinocytes formed new epidermis, hair follicles and sebaceous glands in skin reconstitution experiments, showing that these are HFSCs from the bulge outer root sheath. Taken together, we developed an efficient in vitro system to enrich ovine HFSCs, providing enough HFSCs for the investigations about the ovine hair cycle, aiming to promote wool production in the future.